2021
DOI: 10.1021/jacs.1c06435
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Amino Acids for Hypoxia-Responsive Peptide Self-Assembly and Fluorescence

Abstract: Design of endogenous stimuli-responsive amino acids allows for precisely modulating proteins or peptides under a biological microenvironment and thereby regulating their performance. Herein we report a noncanonical amino acid 2-nitroimidazol-1-yl alanine and explore its functions in creation of the nitroreductase (NTR)-responsive peptide-based supramolecular probes for efficient hypoxia imaging. On the basis of the reduction potential of the nitroimidazole unit, the amino acid was synthesized via the Mitsunobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 61 publications
1
54
0
Order By: Relevance
“…[16,17] Heptamethine cyanine dyes are commonly employed as the molecular scaffold because they have favorable NIR fluorescence properties. [18][19][20][21][22][23][24] But as the field matures and moves toward clinical translation, there is a need to optimize the molecular design and create NTR responsive probes that have a precise combination of favorable photophysical and pharmaceutical properties. [25] Heptamethine cyanine dyes are inherently hydrophobic molecules, and it is a synthetic challenge to design and prepare them as selective NTR probes with high water solubility, along with rapid enzyme-catalyzed kinetics and a high level of "turn on" NIR fluorescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17] Heptamethine cyanine dyes are commonly employed as the molecular scaffold because they have favorable NIR fluorescence properties. [18][19][20][21][22][23][24] But as the field matures and moves toward clinical translation, there is a need to optimize the molecular design and create NTR responsive probes that have a precise combination of favorable photophysical and pharmaceutical properties. [25] Heptamethine cyanine dyes are inherently hydrophobic molecules, and it is a synthetic challenge to design and prepare them as selective NTR probes with high water solubility, along with rapid enzyme-catalyzed kinetics and a high level of "turn on" NIR fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…The research field has progressed from fluorescent probes with visible wavelength emission to probes that absorb and emit NIR light which is known to penetrate further through opaque biological media including skin and tissue [16,17] . Heptamethine cyanine dyes are commonly employed as the molecular scaffold because they have favorable NIR fluorescence properties [18–24] . But as the field matures and moves toward clinical translation, there is a need to optimize the molecular design and create NTR responsive probes that have a precise combination of favorable photophysical and pharmaceutical properties [25]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, peptides were enriched in the liver,w hich was consistent with other nanodrugs. [25] Second, to observe the drug delivery effect of this strategy in vivo,t he nude mice were pretreated with KYp or KY in the tail vein and then injected with Cy5-labeled KLAK. After 24 h, ex vivo FL imaging was performed on the isolated tumor, and the semiquantitive analysis showed that FL intensity at the tumor…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Yu and co-workers designed and synthesized an unconventional amino acid that reacts with NTR (nitro-reductase) to regulate the self-assembly of peptides into a supramolecular probe for morphological transformation, which could be used to efficient hypoxia imaging. (Hu et al, 2021). The nitroimidazole part was integrated into the side chain of alanine, the NTR response amino acid was designed, and the nitro position of the nitroimidazole was optimized to obtain 2-nitroimidazole-1acylalanine with the maximum reduction ability, called A(2NI) (Figure 11A).…”
Section: Imagingmentioning
confidence: 99%